Combining Public Sector and Economic Reform - RUANE, FRANCES (My University, 2012)
This paper argues that it is important for public sector reform to be undertaken in tandem with economic reform because the two reform agendas overlap. Ignoring the overlap could lead to services being delivered efficiently but which do not contribute to economic and social progress or represent value for money. The paper discusses the benefits of policy making in Ireland becoming more evidence based. However, it points to the dearth of relevant data and the need for government departments to engage in building a data infrastructure to underpin the design and implementation of policy. The alternative to an evidence approach is that economic policy decisions can be evidence blind, and based on ideology, fashion or past practice. The paper identifies the risk of reform being undertaken too quickly. It suggests that there is a need to prioritise actions and get the correct pace and sequencing of implementation. This challenge is particularly evident in the health sector. The paper points to the merits of developing a more open dialogue in discussions within the civil service, arguing that this will reduce the risk of ?groupthink? in the future. It suggests two interventions that might help: (a) use of external peer review processes for draft background research documents, and (b) use of a Devil?s Advocate for internal discussions of major policy issues. Finally, the paper discusses the challenges for the civil service of building up specialist skills and replacing the generalist model that has been predominant over the past 30 years with a more multi-skilled model. It illustrates the challenge in relation to economists and the plans in preparation to create the Irish Government Economic and Evaluation Service (IGEES).
PUBLISHED
Keywords: Economics